2013
DOI: 10.3329/bjar.v38i1.15199
|View full text |Cite
|
Sign up to set email alerts
|

Study On Intercropping Leafy Vegetables With Okra (Abelmoschus esculentus L.)

Abstract: A field experiment on intercropping of okra and leafy vegetables was conducted at Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur and Agricultural Research Station, Burirhat, Rangpur during Kharif-I season of 2010 and 2011 to find out suitable crop combination for higher productivity and economic return. Seven treatments viz., sole okra (50 cm × 40cm), okra 100% (in row) + red-amaranth 100% (broadcast), okra 100% (in row) + red-amaranth 75% (broadcast), okra 100% (in row) + leaf amaranth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
5
8
0
Order By: Relevance
“…Quayyum and Maniruzzaman (1995), Islam et al (2006) and Santalla et al (2001) also reported that seed yield was higher in monoculture as compared to their corresponding intercropped yield. The yield loss due to intercropping also reported by Ahmed et al (2013), Muoneke and Ndukwe (2008) and Manga et al (2003).…”
Section: Resultssupporting
confidence: 52%
“…Quayyum and Maniruzzaman (1995), Islam et al (2006) and Santalla et al (2001) also reported that seed yield was higher in monoculture as compared to their corresponding intercropped yield. The yield loss due to intercropping also reported by Ahmed et al (2013), Muoneke and Ndukwe (2008) and Manga et al (2003).…”
Section: Resultssupporting
confidence: 52%
“…Among the treatments, pumpkin including spinach combination was 120 % higher over the sole pumpkin followed by pumpkin+ red amaranth (66%), pumpkin+ mustard green (50%), pumpkin+ radish (49%), pumpkin+ jute green (46%) and pumpkin+ coriander (39%). Increased system productivity was also reported by many authors when leafy vegetables were intercropped with maize (35-63% by Akhtar et al 2015), Brinjal (11-27% by Islam et al 2014 and okra (28-45% by Ahmed et al 2013). Table 3.…”
Section: System Productivitysupporting
confidence: 55%
“…Additional yield of companion crops having a good market price mainly contributed to increase the profitability of intercropping systems over sole pumpkin. Begum et al (2015), Hossain et al (2015), Akhtar et al (2015), Islam et al (2014) and Ahmed et al (2013) also reported that intercropping gave higher productivity and economic returns compared to monoculture. 10.7 Price of input (US $ kg -1 ): Urea: 0.24, TSP: 0.27, MOP: 0.21, Gypsum: 0.12, Zinc sulphate: 2.20 and Boric acid: 4.27, pumpkin seed: 3.66, radish seed: 2.44, red amaranth seed: 2.44, coriander seed: 159, mustard seed: 1.04, spinach seed: 2.44, labour: 3.66 US $, land lease: US $ 40.24 bigha -1 1 US $ = 82 BDT…”
Section: Economic Performancesmentioning
confidence: 94%
“…The negative impact of yield in main crop in intercropping system was reported by Varghese (2013) in cabbage of cabbage plus radish intercropping system. The yield loss due to intercropping was also reported by Begum et al (2015), Ahmed et al (2013) and Muoneke and Ndukwe (2008). Yield advantage: The advantageous effect of ash gourd in intercropping system was expressed by ash gourd equivalent yield and that was influenced by different intercropping systems (Figure 3).…”
Section: Resultsmentioning
confidence: 91%